Empirical Examination of the Relationship Between Cost Efficiency, Capital Structure, and Dividend Policy on the Firm Value of BUMN Karya Construction Companies - Akbar, Dimas Bagus Mahasinul; Nurwati, Etty; Purwanto, Sri; Pangestuti, Dewi Cahyani (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the effect of project cost efficiency, capital structure, and dividend policy on firm value in state-owned enterprises operating in the construction sector in Indonesia. The research is motivated by the decline in financial performance and market valuation of state-owned construction companies (BUMN Karya) amid capital-intensive operations and long-term project-based business characteristics. This study employs a quantitative approach using panel data regression methods. The research objects consist of state-owned construction companies listed on the Indonesian capital market during the 2020–2024 period. The results indicate that cost efficiency has a positive effect on firm value, while capital structure has a negative effect on firm value. Dividend policy is proven to have a positive effect on firm value, indicating the role of dividends as a signal of market confidence. However, the results of the simultaneous test show that cost efficiency, capital structure, and dividend policy jointly do not have a significant effect on firm value. These findings suggest that the firm value of state-owned construction companies is not solely determined by internal policies but is also influenced by external factors such as project risk and industry dynamics. This study provides important managerial implications for management in formulating more adaptive financial policies to enhance firm value sustainably. Keywords: Cost efficiency, Capital structure, Dividend policy, Firm value)